Black Raspberry Inhibits Oral Tumors in Mice Treated with the Tobacco Smoke Constituent Dibenzo(def,p)chrysene via Genetic and Epigenetic Alterations - Chen, Kun-Ming (Cancer Prev Res (Phila), 2020)
We previously reported that the environmental pollutant and tobacco smoke constituent dibenzo[def,p]chrysene (DBP) induced DNA damage, altered DNA methylation and induced oral squamous cell carcinoma (OSCC) in mice. In the present study, we showed that 5% dietary black raspberry (BRB) significantly reduced (p <0.05) the levels of DBP-DNA adducts in the mouse oral cavity with comparable effect to those of its constitutes. Thus, only BRB was selected to examine if aberrant DNA methylation induced by DBP can be altered by BRB. Using comparative genome-wide DNA methylation analysis, we identified 479 hypermethylated and 481 hypomethylated sites (q < 0.01, methylation difference >25%) between the oral tissues of mice treated with DBP and fed control diet or diet containing BRB. Among the 30 differential methylated sites (DMS) induced by DBP, we found DMS mapped to Fgf3, Qrich2, Rmdn2 and Cbarp were hypermethylated by BRB while hypomethylated by DBP at either the exact position or proximal sites; DMS mapped to Vamp3, Ppp1rB1, Pkm, and Zfp316 were hypomethylated by BRB but hypermethylated by DBP at proximal sites. In addition to Fgf3, 2 DMS mapped to Fgf4 and Fgf13 were hypermethylated by BRB; these fibroblast growth factors are involved in regulation of the epithelial-mesenchymal transition pathway (EMT) as identified by IPA. Moreover, BRB significantly reduced (p<0.05) the tumor incidence from 70% to 46.7%. Taken together, the inhibitory effects of BRB on DNA damage combined with its effects on epigenetic alterations may account for BRB inhibition of oral tumorigenesis induced by DBP.